Hubungan antara Disfungsi Tiroid dengan Profil Lipid pada Pasien Struma di Klinik Litbang GAKI Magelang - Yusi Dwi Nurcahyani; Prihatin Broto Sukandar; Raden Edi Fitriyanto; Syaefudin Ali Akhmad (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Relationship between thyroid hormones and lipid profiles in patients with struma is a common condition found in IDD endemic areas. Objective: This study observes relationships between thyroid functions and lipid profiles in woman patients of childbearing age with struma. Methods: This paper is a cross-sectional study of 83 subjects/patients who met inclusion and exclusion criteria in this study. Total cholesterol, LDL, HDL, TSH, and free T4 concentration were measured in all the patients. Lipid concentrations in patients with thyroid dysfunction and patients with euthyroid were compared by using a linear regression model. Results: Total cholesterol, LDL, and HDL was significantly lower in patients with primary hyperthyroidism (N=19) than in patients with euthyroid (N=48) (mean±SD 122.8±20.09 mg/dl vs 187.3±33.66 mg/dl, p=0.000 unadjusted, p= 0.000 adjusted for age and BMI); (63.5±16.33 mg/dl vs 121.7±29.71 mg/dl, p=0.000 unadjusted, p= 0.000 adjusted for age and BMI); (48.8±9.66 mg/dl vs 53.6±8.49 mg/dl, P=0.049 unadjusted, p=0.026 adjusted for age and BMI. Serum total cholesterol and LDL was lower in patients with subclinical hyperthyroidism (N= 14) than in patients with euthyroid (N=48), but it was not statistically significant (181.6±32.07 mg/dl vs 187.3±33.66 mg/dl, p=0.577 unadjusted, P=0.719 adjusted for age and BMI); (110.5±14.83 mg/dl vs 121.7±29.71 mg/dl, p=0.181 unadjusted, p=0.250 adjusted for age and BMI). Serum HDL was similarly elevated in patiemts with subclinical hypothyroidism (N=14) than in patients with euthyroid (N=48), but it was not statistically significant (57.4±11.04 mg/dl vs 53.6±8.49 mg/dl, p=0.185 unadjusted, p=0.229 adjusted for age and BMI).Conclusion: Serum total cholesterol, LDL and HDL was significantly lower in patients with primary hyperthyroidism, but it was not significant for subclinical hyperthyroidism.